The Configuration of GRB2 in Protein Interaction and Signal Transduction - Dingyi Wang; Guoxia Liu; Yuxin Meng; Hongjie Chen; Zu Ye; Ji Jing (Biomolecules, 2024)
Growth-factor-receptor-binding protein 2 (GRB2) is a non-enzymatic adaptor protein that plays a pivotal role in precisely regulated signaling cascades from cell surface receptors to cellular responses, including signaling transduction and gene expression. GRB2 binds to numerous target molecules, thereby modulating a complex cell signaling network with diverse functions. The structural characteristics of GRB2 are essential for its functionality, as its multiple domains and interaction mechanisms underpin its role in cellular biology. The typical signaling pathway involving GRB2 is initiated by the ligand stimulation to its receptor tyrosine kinases (RTKs). The activation of RTKs leads to the recruitment of GRB2 through its SH2 domain to the phosphorylated tyrosine residues on the receptor. GRB2, in turn, binds to the Son of Sevenless (SOS) protein through its SH3 domain. This binding facilitates the activation of Ras, a small GTPase, which triggers a cascade of downstream signaling events, ultimately leading to cell proliferation, survival, and differentiation. Further research and exploration into the structure and function of GRB2 hold great potential for providing novel insights and strategies to enhance medical approaches for related diseases. In this review, we provide an outline of the proteins that engage with domains of GRB2, along with the function of different GRB2 domains in governing cellular signaling pathways. This furnishes essential points of current studies for the forthcoming advancement of therapeutic medications aimed at GRB2.